Implications Of Criminal Law On The Practice Of Witch Curse In Indonesia According To Law Number 1 Of 2007 On The New Criminal Code - Mamonto, Ambarwati (Universitas Pahlawan Tuanku Tambusai, 2024)
This paper analyzes the legal ramifications and efficacy of Article 252 of Law No. 1 of 2023 punishments against illegal black magic in Indonesia's social and legal setting. The paper examines how the new criminal legislation regulates black magic crimes, evidence issues, and societal effects. Research is done using normative legal and descriptive-analytical methods. Legal literature—laws, books, scientific journals, and pertinent articles—provides data. The research found that although Article 252 of Law No. 1 of 2023 legalizes supernatural abilities, their implementation is difficult, particularly in terms of proof. This article's formal crime stresses the perpetrator's supernatural abilities rather than bodily or mental repercussions. However, social abuse of this item might cause horizontal conflict. Thus, law enforcement and the public must grasp the constraints and goals of penalties to make them successful.